An atomic dispersion catalyst for simultaneous removal of nitrogen oxides and volatile organic compounds, a method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202611126993.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-13
AI Technical Summary
尽管如此,目前关于机械化学法制备原子级分散催化剂的研究,大多仅关注球磨时间或转速等单一参数,缺乏对罐体材质、球料比、转速、时间等多参数系统调控,以及这些参数与氧空位浓度、原子级分散程度之间构效关系的深入认识
1. 本发明直接利用机械化学法制备催化剂,通过对罐体材质、球磨时间等参数的独立调控,可在不改变化学组成的前提下系统优化前驱体缺陷密度和Pt分散状态,无需复杂流程或较高的贵金属负载,具备低成本优势。相比化学还原处理,无需废水处理;相比氢气还原处理,避免危险气体使用;相比等离子体轰击,操作更为简单,构建氧空位效率更高;
Smart Images

Figure CN122894984A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of air pollution control technology, specifically relating to an atomically dispersed catalyst for the synergistic removal of nitrogen oxides and volatile organic compounds, its preparation method, and its application. Background Technology
[0002] Nitrogen oxides (NOx) and volatile organic compounds (VOCs) are the main components of PM2.5. 2.5 NOx and VOCs are important precursors to ozone and major contributors to environmental problems such as haze, secondary aerosols, and photochemical smog. Selective catalytic reduction (NH3-SCR) and catalytic oxidation are ideal technologies for industrial removal of NOx and VOCs, respectively. However, using two separate units to treat NOx and VOCs separately presents challenges such as high equipment investment, large footprint, and high operating costs. Given the current focus on the synergistic control of multiple pollutants, achieving the synergistic elimination of NOx and VOCs within an SCR unit has become a more energy-efficient and cost-effective alternative.
[0003] Currently, vanadium-titanium-based catalysts are the most widely used denitrification catalysts due to their excellent denitrification performance and resistance to poisoning, and have been extensively used to treat NOx emissions from stationary sources such as coal-fired power plants. However, these catalysts not only have a toxic active component, V₂O₅, but also generate secondary pollution from spent catalysts; furthermore, their production costs are high, and their denitrification activity temperature window is relatively narrow (only 300~400 °C), severely limiting their application range. In addition, V₂O₅-WO₃ / TiO₂ catalysts exhibit poor VOCs removal performance and are accompanied by the formation of organic byproducts. Therefore, improving the low-temperature activity of catalysts is one of the key challenges in achieving efficient and synergistic removal of NOx and VOCs.
[0004] Noble metal supported catalysts (especially Pt-based catalysts) have shown great potential in NOx reduction and VOCs oxidation due to their excellent low-temperature redox performance and stability. However, the high prices of noble metals such as Pt, Au, and Pd limit their large-scale industrial application. Therefore, if noble metal catalysts are used for the synergistic removal of NO and VOCs from coal-fired flue gas, the key issue is to maximize the atomic utilization rate of the noble metals while ensuring catalytic activity. By anchoring noble metals in an atomically dispersed form on the surface of an oxide support, their utilization efficiency can be significantly improved. At the same time, the synergistic effect of the atomically dispersed metal sites and the oxygen vacancies on the support can promote the adsorption, activation, and electron transfer processes of reactant molecules, which is crucial for improving the catalytic activity of the catalyst for VOCs and NOx. Therefore, constructing oxygen vacancies and achieving a high degree of dispersion of active sites becomes the key to improving the performance of atomically dispersed catalysts.
[0005] However, existing methods for preparing atomically dispersed catalysts (such as impregnation, template methods, and pyrolysis methods) generally suffer from drawbacks such as high energy consumption, high reducing agent consumption, complex processes, and high costs. In contrast, mechanochemical methods are a safer, more controllable, and greener strategy. They utilize mechanical force to induce solid-phase reactions and structural reconstruction in precursors, offering advantages such as simple loading methods, short preparation processes, low calcination temperatures, and small product particle sizes. Nevertheless, current research on the preparation of atomically dispersed catalysts using mechanochemical methods largely focuses on single parameters such as ball milling time or rotation speed, lacking a systematic understanding of the control of multiple parameters such as tank material, ball-to-material ratio, rotation speed, and time, as well as the structure-activity relationship between these parameters and oxygen vacancy concentration and the degree of atomic dispersion. Existing research shows that mechanochemical methods can achieve atomic dispersion of noble metals on oxide supports in one step, but research on controllable oxygen vacancy concentration through systematic adjustment of ball milling parameter combinations for catalytic systems in the synergistic removal of NOx and VOCs remains scarce.
[0006] Therefore, there is an urgent need to develop a catalyst preparation strategy based on mechanochemical methods that can achieve atomic-level dispersion and tunable oxygen vacancies through multi-parameter synergistic control. This strategy will not only help reduce preparation costs but also provide an efficient and green technological path for the synergistic treatment of industrial waste gases. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention aims to overcome these deficiencies by providing an atomically dispersed catalyst for the synergistic removal of nitrogen oxides and volatile organic compounds (VOCs) under low-temperature conditions through the control of ball milling process parameters. The catalyst's preparation method and applications are also described. By systematically controlling ball milling process parameters (tank material, ball-to-material ratio, milling time, rotation speed, etc.), controlled mechanical force is used to construct defects of varying densities in the precursor. After calcination in an air atmosphere, these defects are converted into oxygen vacancies of adjustable concentration, thereby achieving synergistic coupling between atomically dispersed Pt active centers and oxygen vacancies. This enables highly efficient synergistic removal of NOx and VOCs in the medium-to-low temperature range. Furthermore, by introducing MnO2 to construct a Pt-CeO2-MnO2 composite oxide active phase system, the oxygen vacancy concentration and the number of surface-active oxygen species are enhanced. This catalyst can be applied to the synergistic treatment of NOx and VOCs in flue gas from coal-fired power plants, cement plants, metallurgical industries, and other fields, as well as to the selective catalytic reduction of ammonia and the catalytic oxidation of VOCs, significantly improving synergistic removal performance.
[0008] To achieve the above objectives, the technical solution of the present invention includes the following steps: This invention provides an atomically dispersed catalyst for the synergistic removal of nitrogen oxides and volatile organic compounds. The catalyst uses platinum acetylacetone, cerium acetylacetone, and / or manganese acetylacetone as raw materials. The content of the active component Pt in the catalyst is less than 1.0 wt.%, preferably 0.4 wt.%, of the total catalyst mass. When the catalyst is made from platinum acetylacetone and cerium acetylacetone, the active components in the catalyst are CeO2 and atomically dispersed Pt species, with Pt anchored on the CeO2 surface in an atomically dispersed form. When the catalyst is made from platinum acetylacetonate and manganese acetylacetonate, the active components in the catalyst are MnO2 and atomically dispersed Pt species, with Pt anchored on the MnO2 surface in an atomically dispersed form. The catalyst uses cerium acetylacetone, manganese acetylacetone and platinum acetylacetone as raw materials. The active components in the catalyst are CeO2, MnO2 and atomically dispersed Pt species. CeO2 and MnO2 together constitute a composite oxide active phase system that can undergo redox cycles. Pt is anchored on the surface of the composite oxide in an atomically dispersed form. The catalyst is prepared by adjusting the ball milling parameters, which include: the ball milling jar material is selected from stainless steel, zirconium oxide, agate, and tungsten carbide; and the ball milling time is 1 to 15 hours.
[0009] The catalyst is prepared by controlling the parameters of the ball milling process, including the tank material, ball-to-material ratio, milling time and rotation speed. By adjusting the above parameters, the mechanical strength and defect density in the precursor can be controlled. After calcination in an air atmosphere, it is transformed into an oxygen vacancy defect structure with a controllable concentration, thereby achieving the synergistic removal of nitrogen oxides and volatile organic compounds in the medium and low temperature range.
[0010] The material of the grinding jar (stainless steel, zirconium oxide, agate, tungsten carbide) affects the efficiency of collision energy transfer. Stainless steel jars are suitable for this system due to their moderate hardness and good wear resistance. The grinding time is 1~15 hours; too short a time results in insufficient defects, while too long a time causes excessive structural damage; 10 hours is preferred.
[0011] Preferably, the ball-to-material ratio is controlled between 2:1 and 10:1. If it is too low, the collision energy will be insufficient, and if it is too high, it may cause over-grinding; 7:1 is preferred. The ball milling speed is 200 to 600 rpm. If the speed is too low, the defect formation will be slow, and if it is too high, it may cause phase change or agglomeration; 400 rpm is preferred.
[0012] It should be noted that the Pt species in the catalyst are highly dispersed on the CeO2 / MnO2 support surface in the form of single atoms or sub-nanometer clusters, thereby maximizing the utilization rate of noble metal atoms. Essentially, the catalyst is Pt supported on CeO2 / MnO2, and the core requirement is that the Pt content must be less than 1.0 wt.% of the total catalyst mass, preferably 0.4 wt.%. This is because when the Pt content is too high, it easily forms clusters, and thus is not atomically dispersed.
[0013] Preferably, by adjusting the ball milling parameter combination and combining it with air atmosphere calcination, an oxygen vacancy defect structure with an adjustable concentration is formed on the surface of the catalyst. The oxygen vacancies and atomically dispersed Pt active centers work synergistically to promote the reduction and conversion of nitrogen oxides and the oxidative decomposition of volatile organic compounds.
[0014] The present invention also provides a method for preparing the above-mentioned atomically dispersed catalyst for synergistic removal of nitrogen oxides and volatile organic compounds, comprising the following steps: a. Mix platinum acetylacetone, cerium acetylacetone and / or manganese acetylacetone in proportion and place in a ball mill jar. Add grinding balls, level the ball mill jar and place it in a planetary ball mill. Mill for 1 to 15 hours to obtain the precursor. b. The precursor is placed in a tube furnace and calcined in air atmosphere, with the temperature increased to 300 °C at a heating rate of 1~10 °C / min, and calcined for 2 hours to obtain an atomically dispersed catalyst that synergistically removes nitrogen oxides and volatile organic compounds.
[0015] Preferably, in step a, the purity of cerium acetylacetone, manganese acetylacetone, and platinum acetylacetone is not lower than analytical grade, wherein the platinum content is 0.4 wt.% of the total mass of the catalyst.
[0016] Preferably, in step a, the grinding jar is made of one of stainless steel, zirconium oxide, agate, or tungsten carbide, with stainless steel being the most preferred. Different jar materials provide different collision energy transfer efficiencies, thereby affecting the mechanical strength and defect formation rate of the precursor.
[0017] Preferably, in step a, the ball milling time is 1 h, 5 h, 10 h, or 15 h; more preferably 10 h. A ball milling time that is too short will not produce sufficient defects, while a time that is too long may lead to Pt species aggregation or excessive damage to the carrier structure.
[0018] Preferably, in step a, the ball-to-material ratio is 7:1, and the grinding balls are made of different particle size combinations (including 1 cm, 0.7 cm, 0.3 cm and 0.1 cm steel balls) to optimize the collision frequency and energy distribution, and improve the uniformity and defect density of the precursor.
[0019] Preferably, in step a, the rotational speed is 400 rpm. Too low a speed results in insufficient mechanical force, while too high a speed may lead to localized overheating and structural collapse.
[0020] Preferably, in step a, the ball mill is paused every hour during the ball milling process, the ball mill jar is removed, and the powder adhering to the wall is scraped off with a spatula to prevent the powder from clumping under mechanical force and to ensure the uniformity of the precursor.
[0021] Preferably, in step b, the calcination atmosphere is air, and the heating rate is 2 °C / min.
[0022] This invention also provides the application of the above-mentioned atomically dispersed catalyst for the synergistic removal of nitrogen oxides and volatile organic compounds. By utilizing the synergistic effect of oxygen vacancy defects on the catalyst surface and atomically dispersed Pt active centers, the catalyst is used for the synergistic removal of nitrogen oxides and volatile organic compounds in industrial flue gas.
[0023] Preferably, the catalyst uses cerium acetylacetone, manganese acetylacetone, and platinum acetylacetone as raw materials, and the catalyst has a volume hourly space velocity (VHSV) of not less than 120,000 h⁻¹. -1 Under O2 / N2 atmosphere conditions of NO concentration not less than 400 ppm, volatile organic compound concentration of organic compounds represented by toluene not less than 50 ppm, and oxygen volume fraction not higher than 5 vol.%, the conversion rate of nitrogen oxides is not less than 80% within a temperature window of 100~240 ℃; the toluene conversion rate reaches 50% at 103 ℃ and 90% at 191 ℃.
[0024] Preferably, the catalyst can be applied to the industrial waste gas purification process in industries such as coal-fired power plants, cement, and metallurgy to achieve synergistic control of multiple pollutants.
[0025] Compared with the prior art, the present invention has the following obvious and prominent substantive features and significant advantages: 1. This invention directly utilizes a mechanochemical method to prepare catalysts. By independently controlling parameters such as tank material and ball milling time, the defect density of the precursor and the Pt dispersion state can be systematically optimized without changing the chemical composition. It eliminates the need for complex processes or high precious metal loading, offering a low-cost advantage. Compared to chemical reduction, it eliminates the need for wastewater treatment; compared to hydrogen reduction, it avoids the use of hazardous gases; and compared to plasma bombardment, it is simpler to operate and more efficient at creating oxygen vacancies. 2. By rationally combining ball milling parameters, the oxygen vacancy concentration on the catalyst surface can be controlled: Under the combined conditions of ball milling for 10 hours and stainless steel tank (more preferably, rotation speed of 400 rpm and ball-to-material ratio of 7:1), the atomically dispersed catalyst has the highest specific surface area and oxygen vacancy concentration, and the number and migration ability of surface active oxygen species are improved, which significantly improves the adsorption, activation and conversion efficiency of reactants. 3. The synergistic effect of atomically dispersed Pt active centers and oxygen vacancy defects enables the simultaneous reduction of nitrogen oxides and oxidation of volatile organic compounds, thus broadening the effective reaction temperature window of the catalyst. 4. Further introduction of MnO2 to construct a Pt-CeO2-MnO2 composite oxide system enhances the oxygen vacancy concentration and the number of surface active oxygen species. In the low temperature range of 100~240 ℃, the catalyst exhibits the best catalytic activity in the synergistic removal of NO and toluene, and has broad prospects for industrial application. Attached Figure Description
[0026] One or more embodiments are illustrated by way of example with reference to the accompanying drawings. These illustrations do not constitute a limitation on the embodiments, and unless otherwise stated, the figures in the drawings are not to be limited by scale.
[0027] Figure 1 X-ray diffraction (XRD) patterns of Pt-CeO2-Xh and Pt-CeO2-MnO2-10h catalysts prepared for different ball milling times; Figure 2 The image shows an atomic resolution HAADF-STEM image of the Pt-CeO2-10h catalyst prepared in Example 1. Figure 3 The EXAFS spectrum of the Pt-CeO2-10h catalyst prepared in Example 1 is shown below. Figure 4 Conversion curves of synergistic removal of NO and toluene by Pt-CeO2-Xh catalysts prepared for different ball milling times; Figure 5 Conversion curves for the synergistic removal of NO and toluene by different metal oxide catalysts; Figure 6 EPR spectra of Pt-CeO2-Xh and Pt-CeO2-MnO2-10h catalysts prepared for different ball milling times; Figure 7 O1s spectra of XPS catalysts prepared for different ball milling times for Pt-CeO2-Xh and Pt-CeO2-MnO2-10h. Detailed Implementation
[0028] The present invention will now be described in detail with reference to specific embodiments.
[0029] The preferred range and control principles of the ball milling process parameters described in this invention are as follows: The material of the ball mill jar (stainless steel, zirconium oxide, agate, tungsten carbide) affects the collision energy transfer efficiency. Stainless steel jars are suitable for this system due to their moderate hardness and good wear resistance. The ball-to-material ratio should be controlled between 2:1 and 10:1; too low a ratio results in insufficient collision energy, while too high a ratio may lead to over-grinding; 7:1 is preferred. The ball milling speed should be between 200 and 600 rpm; too low a speed results in slow defect formation, while too high a speed may induce phase transformation or agglomeration; 400 rpm is preferred. The ball milling time should be between 1 and 15 hours; too short a time results in insufficient defects, while too long a time leads to excessive structural damage; 10 hours is preferred. Through synergistic optimization of the above parameters, the distribution of active components and defect density in the precursor can be precisely controlled, thereby controlling the final catalyst active site distribution and oxygen vacancy concentration.
[0030] Example 1 In this embodiment, a method for preparing an atomically dispersed catalyst Pt-CeO2-10h for synergistic removal of NO and VOCs is described below: a. Weigh 5.0628 g of cerium acetylacetone powder and 0.0161 g of platinum acetylacetone powder into a mortar and grind them evenly with a grinding rod. Then pour the mixture into a stainless steel ball mill jar. Place 5 1 cm steel balls, 5 0.7 cm steel balls, 10 0.3 cm steel balls, and 10 0.1 cm steel balls into the ball mill jar, controlling the ball-to-powder ratio to be 7:1. Place the ball mill jar diagonally in a planetary ball mill and ball mill at 400 r / min for 10 h. To prevent the powder from adhering to the wall of the ball mill jar and agglomerating under mechanical force, pause the ball mill every 1 h, remove the ball mill jar, and scrape off the powder from the wall with a spatula to prevent agglomeration and ensure the uniformity of the precursor.
[0031] b. The Pt-CeO2-10h precursor obtained after ball milling was poured into an alumina crucible and placed in a tube furnace. The furnace was heated to 300 °C at a heating rate of 2 °C / min under air atmosphere, calcined at this temperature for 2 h, and then naturally cooled to room temperature to obtain an atomically dispersed catalyst. The obtained catalyst was tableted, crushed, and sieved to 40–60 mesh for later use.
[0032] XRD pattern analysis shows that ( Figure 1 The main crystalline phase composition of the Pt-CeO2-10h catalyst obtained in this embodiment is cerium dioxide (CeO2, PDF#34-0394), and no characteristic diffraction peaks representing platinum species were detected, indicating that the Pt species are highly dispersed on the CeO2 support. HAADF-STEM ( Figure 2 EXAFS spectrum Figure 3Further analysis confirmed that Pt species were anchored on the CeO2 surface in an atomically dispersed form.
[0033] Catalytic performance test 0.1 g of the sieved catalyst was placed in a fixed-bed quartz tube reactor. The reaction temperature was adjusted from 100 °C to 300 °C using a temperature controller. After the NO and toluene concentrations at the outlet reached a stable state, the outlet gas was analyzed. The gas hourly space velocity (GHSV) for this experiment was set to 120,000 h⁻¹. -1 The inlet gas composition was: 5 vol.% O2, 50 ppm C7H8, 400 ppm NH3, and 400 ppm NO, with N2 as the balance gas. The NO and NH3 concentrations at the fixed bed outlet were analyzed using Fourier transform infrared spectroscopy, and the toluene concentration was analyzed using gas chromatography. Under these test conditions, the catalyst denitrification efficiency and VOCs conversion efficiency are shown in Table 1 below.
[0034] Comparative Example 1 (ball milling time 1 h) The raw materials, preparation method and process conditions used in Comparative Example 1 were exactly the same as those in Example 1. The only difference was that the ball milling time was adjusted to 1 h and the ball mill jar was not opened to scrape powder during the ball milling process. All other conditions remained unchanged, and the catalyst of Comparative Example 1 was obtained and named Pt-CeO2-1h.
[0035] Catalytic performance test The obtained catalyst was subjected to catalytic performance testing under the same reaction conditions as in Example 1. The results showed that the synergistic removal performance of the Pt-CeO2-1h catalyst for NOx and toluene was significantly lower than that of Example 1 within the test temperature range. The NO conversion efficiency was below 40% in most temperature ranges, and the temperature at which toluene reached 90% conversion was much higher than that in Example 1. This indicates that the short ball milling time cannot introduce enough defect sites in the catalyst precursor, thereby limiting the formation of oxygen vacancies and the catalytic activity.
[0036] Comparative Example 2 (ball milling time 5 h) The raw materials, preparation method and process conditions used in Comparative Example 2 were exactly the same as those in Example 1, except that the ball milling time was adjusted to 5 h, while the other conditions remained unchanged, and the catalyst of Comparative Example 2 was obtained and named Pt-CeO2-5h.
[0037] Catalytic performance test The catalytic performance was evaluated under the same reaction conditions. The results showed that the synergistic removal performance of the catalyst for NOx and toluene within the test temperature range was between that of Example 1 and Comparative Example 1, with a maximum NO conversion of 52.1% and a toluene conversion of [missing value]. 90The temperature was 214.34 ℃, indicating that although a ball milling time of 5 h can introduce a certain number of defect sites, the optimal oxygen vacancy concentration has not yet been reached.
[0038] Comparative Example 3 (ball milling time 15 h) The raw materials, preparation method and process conditions used in Comparative Example 3 were exactly the same as those in Example 1, except that the ball milling time was adjusted to 15 h, while the other conditions remained unchanged, and the catalyst of Comparative Example 3 was obtained and named Pt-CeO2-15h.
[0039] Catalytic performance test The catalytic performance was evaluated under the same reaction conditions. The results showed that after extending the ball milling time to 15 h, the synergistic removal performance of the catalyst decreased compared with Example 1, indicating that excessively long ball milling time may lead to the aggregation of Pt species or excessive destruction of the support structure, which is detrimental to the synergistic effect of oxygen vacancies and active sites.
[0040] Example 2 (Single metal oxide Pt-MnO2) This embodiment provides a method for preparing atomically dispersed catalysts of single metal oxides using a mechanochemical approach. The specific steps are as follows: a. Weigh 4.0355 g of manganese acetylacetone powder and 0.0081 g of platinum acetylacetone powder into a mortar and grind them evenly with a grinding rod. Then pour the mixture into a stainless steel ball mill jar. Place four 1 cm steel balls, four 0.7 cm steel balls, eight 0.3 cm steel balls, and eight 0.1 cm steel balls into the ball mill jar, controlling the ball-to-powder ratio to be 7:1. Place the ball mill jar diagonally in a planetary ball mill and mill at 400 r / min for 10 h. To prevent the powder from adhering to the wall of the ball mill jar and agglomerating under mechanical force, pause the ball mill every 1 h, remove the ball mill jar, and scrape off the powder from the wall with a spatula.
[0041] b. The Pt-MnO2-10h precursor obtained after ball milling was poured into an alumina crucible and placed in a tube furnace. Under air atmosphere, the temperature was increased to 300 °C at a heating rate of 2 °C / min, and calcined at this temperature for 2 h. After natural cooling to room temperature, an atomically dispersed catalyst was obtained, named Pt-MnO2-10h. The obtained catalyst was tableted, crushed, and sieved, and 40–60 mesh particles were used for catalytic performance evaluation.
[0042] Catalytic performance test Performance tests were conducted under the same reaction conditions as in Example 1. The results (Table 2) show that the Pt-MnO2-10h catalyst exhibits better performance in the NO removal test alone (T). 90 At 160.2 °C, the highest NO conversion rate reached 96.9%; in the synergistic removal test of NO and toluene, the highest NO conversion rate was 80%, and the toluene conversion rate was [missing information].90 The temperature was 231 °C, which showed good NO removal activity, but the toluene oxidation performance was relatively insufficient.
[0043] As can be seen from Examples 1 and 2, the method for preparing the atomically dispersed catalyst for synergistic removal of nitrogen oxides and volatile organic compounds provided by the present invention is applicable to various metal oxide supports.
[0044] Example 3 (Composite oxide Pt-CeO2-MnO2) This embodiment provides a method for preparing multi-metal oxide composite atomically dispersed catalysts using a mechanochemical approach. The specific steps are as follows: a. Weigh 2.1832 g of manganese acetylacetone powder, 1.162 g of cerium acetylacetone powder, and 0.0161 g of platinum acetylacetone powder into a mortar and grind them evenly with a grinding rod. Then pour the mixture into a stainless steel ball mill jar. Place 3 1 cm steel balls, 3 0.7 cm steel balls, 6 0.3 cm steel balls, and 6 0.1 cm steel balls into the ball mill jar, controlling the ball-to-powder ratio to be 7:1. Place the ball mill jar diagonally in a planetary ball mill and mill at 400 r / min for 10 h. To prevent the powder from adhering to the wall of the ball mill jar and clumping under mechanical force, pause the ball mill every 1 h, remove the ball mill jar, and scrape off the powder from the wall with a spatula.
[0045] b. The Pt-CeO2-MnO2-10h precursor obtained after ball milling was poured into an alumina crucible and placed in a tube furnace. The furnace was heated to 300 °C at a heating rate of 2 °C / min under air atmosphere, calcined at this temperature for 2 h, and then naturally cooled to room temperature to obtain an atomically dispersed composite oxide catalyst, named Pt-CeO2-MnO2-10h. The obtained catalyst was tableted, crushed, and sieved, with 40–60 mesh particles used for catalytic performance evaluation.
[0046] Catalytic performance test Performance tests were conducted under the same reaction conditions as in Examples 1 and 2. Figure 4 and Figure 5 The results showed that the Pt-CeO2-MnO2-10h catalyst exhibited excellent catalytic activity in the synergistic removal of NO and toluene, and the T values of NO and toluene were [not specified]. 90 The temperatures were 103 °C and 191 °C, respectively, both much lower than the catalysts prepared in Examples 1 and 2, demonstrating excellent low-temperature activity and wide temperature window characteristics.
[0047] Table 1. Removal performance of catalysts with different ball milling times for NO and toluene, both individually and synergistically.
[0048] Table 2. Removal performance of different metal oxide catalysts for NO and toluene, both individually and synergistically.
[0049] Comparing the experimental results of Examples 1 to 3 (Tables 1 and 2), it can be seen that, under the same ball milling time conditions, the composition of the catalyst active components has a significant impact on the synergistic removal performance. The composite synergistic effect of CeO2 and MnO2 enhances the oxygen vacancy concentration and the number of surface active oxygen species, while the atomically dispersed Pt species further provides highly efficient reactive centers. The synergistic effect of the three achieves the optimal synergistic removal performance of NOx and VOCs.
[0050] To further perform qualitative and quantitative analysis of the oxygen vacancy content, the catalyst was characterized by EPR and O1sXPS, respectively. EPR test results ( Figure 6 The results show that Pt-CeO2-10h exhibits a stronger paramagnetic signal at g=2.003 than Pt-CeO2-1h, indicating a higher oxygen vacancy concentration. Pt-CeO2-MnO2-10h shows the strongest paramagnetic signal at this point, indicating that the introduction of Mn further increases the oxygen vacancy concentration. (O1s XPS spectrum) Figure 7 After peak fitting, two characteristic peaks were observed: lattice oxygen (O) latt 529.7~529.8 eV) and surface chemically adsorbed oxygen (O ads (532.1~532.5 eV). Quantitative analysis showed that the O2 content of Pt-CeO2-10h was... ads / O latt The ratio reached 0.77, higher than that of Pt-CeO2-1h (0.74) and Pt-CeO2-15h (0.76), and the O2 ratio of Pt-CeO2-MnO2-10h. ads / O latt The ratio was further improved to 0.81. These characterization results confirm that by optimizing the combination of ball milling parameters (stainless steel jar, ball-to-material ratio 7:1, rotation speed 400 rpm, time 10 h), mechanical force introduces high-density defects into the precursor. During calcination in an air atmosphere, the escape of lattice oxygen forms a large number of oxygen vacancies. These oxygen vacancies can not only directly participate in the catalytic reaction as active sites, but also promote the adsorption and activation of gaseous oxygen molecules, generating more highly reactive O. ads This significantly improves the low-temperature activity and synergistic removal efficiency of the catalyst by introducing specific species.
[0051] In summary, this invention provides an atomically dispersed catalyst for the synergistic removal of nitrogen oxides and volatile organic compounds, its preparation method, and its applications. By systematically controlling the ball milling process parameters and utilizing a mechanochemical method combined with air calcination, an atomically dispersed Pt-CeO2-MnO2 composite oxide active phase system with adjustable oxygen vacancy concentration was constructed, thereby achieving highly efficient synergistic removal of nitrogen oxides and volatile organic compounds under medium and low temperature conditions.
[0052] The catalyst preparation process described in this invention is simple, the parameters are flexible, the raw materials are widely available, and the cost is low. The resulting catalyst has good synergistic removal performance, a wide reaction temperature window, and high stability. It is suitable for various industrial flue gas purification scenarios such as coal-fired power plants, cement plants, and metallurgical plants, and has significant engineering application value and promotion prospects.
[0053] It should be noted that the specific embodiments of the present invention described above are merely illustrative of the technical principles of the present invention and are not intended to limit the scope of protection of the present invention. Any equivalent modifications or improvements made by those skilled in the art to the structural form, preparation parameters, or application conditions without departing from the technical concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. An atomically dispersed catalyst for the synergistic removal of nitrogen oxides and volatile organic compounds, characterized in that, The catalyst is made from platinum acetylacetone, cerium acetylacetone, and / or manganese acetylacetone; the content of the active component Pt in the catalyst is less than 1.0 wt.%, preferably 0.4 wt.% of the total mass of the catalyst. When the catalyst is made from platinum acetylacetone and cerium acetylacetone, the active components in the catalyst are CeO2 and atomically dispersed Pt species, with Pt anchored on the CeO2 surface in an atomically dispersed form. When the catalyst is made from platinum acetylacetonate and manganese acetylacetonate, the active components in the catalyst are MnO2 and atomically dispersed Pt species, with Pt anchored on the MnO2 surface in an atomically dispersed form. The catalyst uses cerium acetylacetone, manganese acetylacetone and platinum acetylacetone as raw materials. The active components in the catalyst are CeO2, MnO2 and atomically dispersed Pt species. CeO2 and MnO2 together constitute a composite oxide active phase system that can undergo redox cycles. Pt is anchored on the surface of the composite oxide in an atomically dispersed form. The catalyst is prepared by adjusting the ball milling parameters, which include: the ball milling jar material is selected from stainless steel, zirconium oxide, agate, and tungsten carbide; and the ball milling time is 1 to 15 hours.
2. A method for preparing an atomically dispersed catalyst for the synergistic removal of nitrogen oxides and volatile organic compounds according to claim 1, characterized in that, The preparation method includes: a. Mix platinum acetylacetone, cerium acetylacetone and / or manganese acetylacetone in proportion and place in a ball mill jar. Add grinding balls, level the ball mill jar and place it in a planetary ball mill. Mill for 1 to 15 hours to obtain the precursor. b. The precursor is placed in a tube furnace and calcined in air atmosphere, heated to 300 °C at a heating rate of 1~10 °C / min, and calcined for 2 hours to obtain the atomically dispersed catalyst for synergistic removal of nitrogen oxides and volatile organic compounds.
3. The preparation method according to claim 2, characterized in that, The purity of the raw materials cerium acetylacetone, manganese acetylacetone, and platinum acetylacetone in step a shall not be lower than that of analytical grade.
4. The preparation method according to claim 2, characterized in that, In step a, the grinding jar is made of stainless steel; the grinding time is 1 h, 5 h, 10 h or 15 h, preferably 10 h.
5. The preparation method according to claim 2, characterized in that, In step a, the ball-to-material ratio is 2:1 to 10:1, preferably 7:1, and the grinding balls use different particle size combinations, including 1 cm steel balls, 0.7 cm steel balls, 0.3 cm steel balls and 0.1 cm steel balls.
6. The preparation method according to claim 2, characterized in that, In step a, the rotational speed is 200~600 rpm, preferably 400 rpm.
7. The preparation method according to claim 2, characterized in that, In step a, pause the ball mill for 5 minutes every hour during the ball milling process to reduce the occurrence of cold welding.
8. The preparation method according to claim 2, characterized in that, The heating rate in step b is 2℃ / min.
9. The application of the atomically dispersed catalyst for synergistic removal of nitrogen oxides and volatile organic compounds as described in claim 1 in the synergistic removal of nitrogen oxides and volatile organic compounds from industrial flue gas.
10. The application according to claim 9, characterized in that, The catalyst uses cerium acetylacetone, manganese acetylacetone, and platinum acetylacetone as raw materials, and the catalyst has a volume hourly space velocity (VHSV) of not less than 120,000 h⁻¹. -1 Under O2 / N2 atmosphere conditions of NO concentration not less than 400 ppm, toluene concentration not less than 50 ppm, and oxygen volume fraction not more than 5 vol.%, the conversion rate of nitrogen oxides is not less than 80% within a temperature window of 100~240 ℃, the conversion rate of toluene reaches 50% at 103 ℃ and 90% at 191 ℃.